General Geology of Dabong and Rock Coating as a Record of Environmental Changes - Abdul Rahman Mat Jusoh (2019)
Fat crystallization studies are important from both technological and academic points ofview. Understanding the effects of formulation and process factors on the kinetics ofcrystallization is important to control of product quality in industry. This application is to study the solidification phenomena of cow fat using Avrami method byconsider the factor which is the effect of the difference cold temperature and difference mass of fat and compare the solidification mechanism. The percentage of solidification was measured started at first two minute of the solidification until the complete solidification of all parameter. Percentage of the solid was measured and recorded and Avrami equation is apply in order to determine the growth rate and crystallization form. To study the effect of the cold temperature, the weight of the fat was kept constant at 28 g and the temperature of the fat was being set at the 70°C which is the fat is in liquid form. As cold temperature decreased the percentage of solidification increased which the lower temperature which is 10°C is the higher percentage value which is 49.28% follow by 15°C and 20°C which is 35.35% and 30.71% respectively. Have a same value of n=3 that consider the crystallization form of spherulitic growth from instantaneous nucleation or disc-like that in sporadic nucleation form. Smaller volume used have the higher degree of solidification and occur in short time because of the decreasing resistance caused by air bubbles and increased air space volume for arrangement of solid crystal structure to easily occur. The study recorded, The smaller mass of the fat which is 10 g have the higher degree of the solidification percentage was recorded which is (61.8%) compare to other difference mass, 20 g and 30 g that have (51.61%) and (48.67%) respectively. Overall, the higher percentage of solidification will be in lowest temperature and mass of the fat.